Determination of engineering properties of onion crop required for designing an onion harvester. Issue 1 (31st December 2023) - Kumawat, Lokesh; Raheman, Hifjur
Abstract: The knowledge of the engineering properties of the onion bulb is a prerequisite to designing machinery for harvesting and post-harvest operations. The agronomical, mechanical, and biometric properties of the onion crop were measured for the Pusa Red variety at the harvesting stage. Onion ( Allium cepa L.) seedlings of Pusa Red variety were grown at 150-mm row-to-row and 100-mm plant-to-plant spacing in sandy loam soil. The onion bulbs were obtained within 69.15 ± 7.17 mm below the ground surface with a coefficient of variation (CV) of 10.37%. The average length of onion plants was found to be 236.5 ± 35.28 mm with a CV of 14.91%. The cutting force required to cut the leaves from the onion was in the range of 45.42–105.87 N. The pulling force required to dig out the bulbs at the mean depth of 70 mm was found to be 32.33 ± 3.05 N. The shape of Pusa Red onion bulbs was found to be of prolate shape. The average values of polar diameter, equatorial diameter, and mass for the large onion bulbs were found to be 57.83 ± 5.26 mm, 46.88 ± 3.29 mm, and 65.68 ± 4.22 g, respectively, as compared to 47.44 ± 2.46 mm, 43.81 ± 3.33 mm, and 47.51 ± 7.07 g, for small onion bulbs. The average value of bulk density for the large and small onion bulbs was found to be 403 and 501.33 kg m −3, respectively. The mean value of angle of repose for small-size bulbs was obtained at 29.2°. A linear relationship was found to exist between polar and equatorial diameters as well as the mass of the bulb and polar/equatorial diameter for both large and small size onion bulbs.